Utilization of Artificial Intelligence for Recruitment of the Best Educational Talent - Unzilah Khomairotusshiyama; Hefniy Hefniy; Eka Diana (Al-Qalam Institute, 2025)
This research explores using artificial intelligence (AI) to support the recruitment process of the best talent in the education sector. Using a quantitative descriptive approach, data was collected through surveys of educational institutions and analysis of documents related to AI implementation. Data analysis techniques include descriptive statistical analysis to measure the acceptance of AI technology and its impact on selection efficiency, global search of candidates, and recruitment diversity. The results show that talent intelligence, including academic ability, creativity, problem-solving skills, and emotional intelligence, is an important factor in selecting prospective teachers. In addition, applying application tracking systems (ATS) and AI in recruitment management facilitates acquiring the right talent. These findings imply the importance of integrating AI technology in recruitment strategies to improve recruitment results quality and strengthen educational institutions' competitiveness in the digital era.